PERAN DAN KONTRIBUSI TENAGA KERJA WANITA SEBELUM DAN SELAMA COVID-19 PADA USAHA PENGOLAHAN RAJUNGAN (STUDI KASUS UD. SINAR SARINA AFA DI KELURAHAN WATOLO KECAMATAN MAWASANGKA KABUPATEN BUTON TENGAH) - D. Diana; N. Nurdiana A; R. Rosmawati (Jurnal Sosial Ekonomi Perikanan, 2022)
Female workers play critical roles in fisheries processing plant thus their contribution to household income.  However, Covid-19 pandemic may cut these contribution due to the declining of fisheries production that reduce the hours of female workers. The purpose of this study was to determine the role of women workers at UD. Sinar Sarina Afaand their contribution on household income before and during Covid-19.This research was conducted at UD. Sinar Sarina Afa is in Watolo Village, Mawasangka District, CentralButon Regency in February – March 2021. The method used in this research was a case study with all female workers at UD. Sinar Sarina Afa as respondents Data were collected through interviews using questionnaires to obtain primary data of respondents, their roles in mini plant and their income.  The data obtained were analyzed using the Harvard Analytical Framework method and income contribution formula.The results showed that before and during Covid-19, female had similar roles in crab processing activities including the stripping, sorting, packaging and cooling processes. During pandemic, the contribution of women in the household income changed from 48% before the pandemic to 42%.   This study showed that the role of female in household is important in increasing family income. Keywords : female; processing; blue swimming crab; mini plant